Certain extensions of the class of stable distributions - Mišeikis, F. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ф. Мишейкис. Некоторые расширения класса устойчивых законовF. Mišeikis. Kai kurie stabilių dėsnių klasės praplėtimai